Soren Kierkegaard : subjectivity, irony, and the crisis of modernity - Stewart, Jon (Jon Bartley) (Oxford University Press, 2015)
'Soren Kierkegaard: subjectivity, irony, and the crisis of Modernity' examines the thought of Soren Kierkegaard, a unique figure, who has inspired, provoked, fascinated and irritated people ever since he walked the streets of Copenhagen. At the end of his life, Kierkegaard said that the only model he had for his work was the Greek philosopher Socrates. This work takes this statement as its point of departure. Jon Stewart explores what Kierkegaard meant by this and to show how different aspects of his writing and argumentative strategy can be traced back to Socrates. The main focus is 'The Concept of Irony,' which is a key text at the beginning of Kierkegaard's literary career. Although it was an early work, it nevertheless played a determining role in his later development and writings. Indeed, it can be said that it laid the groundwork for much of what would appear in his later famous books such as 'Either/Or' and 'Fear and Trembling.'